Acoustical Evaluation of the Itacuruçá Baptist Evangelical Church - Torres, Julio Cesar Boscher (International Journal of Architectural Engineering Technology, 2022)
This paper presents the acoustical evaluation of a representative evangelical church in Rio de Janeiro, Brazil. The analysis, performed through measurements and simulations, has shown that the acoustic field needs to be more appropriate for the temple’s actual use. The analysis measured the impulse responses at 14 positions from 2 source locations and calculated Reverberation Time and Clarity Factor acoustic parameters. According to the literature and the ISO standards, the Reverberation Time was considered higher than the optimum value for both speech or music. An acoustic model for the temple was developed using the BRASS simulator. The simulation results were compared to measured data to validate the acoustic model. Based on that and aiming to achieve optimum acoustic parameters, a new model was proposed to evaluate alternatives to adequate the acoustical characteristics of the temple. The strategy to develop the final model and to achieve the target Reverberation Time is presented and discussed. An acoustic intervention is then proposed and evaluated using simulated data. The results obtained with the proposed changes, which considered the inclusion of perforated panels and carpet in some walls, were adequate, providing Reverberation Time in accordance to the standards and significant improvement to Clarity for music and speech.